2019
DOI: 10.1038/s41598-018-38248-1
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvasculature and Visual Acuity after Intravitreal Aflibercept in Diabetic Macular Edema: An Optical Coherence Tomography Angiography Study

Abstract: We investigated changes in retinal vascular area and the foveal avascular zone (FAZ) after intravitreal aflibercept in diabetic macular edema (DME) and the association of these changes with visual outcomes. The retinal vascular area in the superficial capillary plexus (SCP) and the deep capillary plexus (DCP) and the FAZ area were measured using optical coherence tomography angiography (OCTA) in 23 eyes of 23 patients with DME, before and after intravitreal aflibercept. Overall, there was no significant change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…In another retrospective study that analyzed the FAZ area and vascular changes in the 3 X 3 mm macular area following aflibercept injections (mean: 2.6 ± 1.3 injections) for DME using OCTA, there was enlargement of the FAZ area in the superficial capillary plexus from 0.41 ± 0.2 mm 2 to 0.48 ± 0.24 mm 2 but a decrease in the FAZ area in the deep capillary plexus from 0.75 ± 0.34 mm 2 to 0.71 ± 0.33 mm 2 . Both changes, however, were not statistically significant and the retinal vascular density was unchanged following the injections [ 48 ]. The study included a total of 23 eyes following the exclusion of ineligible eyes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another retrospective study that analyzed the FAZ area and vascular changes in the 3 X 3 mm macular area following aflibercept injections (mean: 2.6 ± 1.3 injections) for DME using OCTA, there was enlargement of the FAZ area in the superficial capillary plexus from 0.41 ± 0.2 mm 2 to 0.48 ± 0.24 mm 2 but a decrease in the FAZ area in the deep capillary plexus from 0.75 ± 0.34 mm 2 to 0.71 ± 0.33 mm 2 . Both changes, however, were not statistically significant and the retinal vascular density was unchanged following the injections [ 48 ]. The study included a total of 23 eyes following the exclusion of ineligible eyes.…”
Section: Resultsmentioning
confidence: 99%
“…This probably reflects the current uncertainty surrounding the effect of these agents on the macular perfusion of diabetics, which prompted many researchers to attempt to resolve this uncertainty using the new and promising OCTA technology considering its perceived advantages in imaging the retinal microvasculature over conventional FA due to its ability to image capillary details, including the deep capillary plexus, in higher resolution without obscuration by dye leakage which allows better delineation and quantification of capillary non-perfusion areas [ 58 , 59 ]. Regarding studies done using OCTA, 3 studies showed stable macular perfusion following injections [ 47 , 49 , 53 ], 6 studies showed worsening macular perfusion following injections [ 15 , 31 , 46 , 51 , 52 , 54 ], and 2 studies showed conflicting results [ 48 , 50 ]. This may have been due to differences in study design, patient inclusion criteria, or method of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of macular disorders is crucial as close monitoring allows for intervention before irreversible damage occurs. The earlier the VD is detected, the better the treatment of the macular disorder can be managed [7]. Currently, various imaging methods including Optical Coherence Tomography (OCT) are used as the standard assessment tools to monitor the progress of the macular disorders [8].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 A few smaller studies have looked at the impact of anti-VEGF injections using optical coherence tomography (OCTA) but these studies have often been limited by smaller sample sizes, combined with different underlying diseases, different types of anti-VEGF agents, and segmentation error. 3 , 4 In this issue, Mirshahi and colleagues evaluated the quantitative changes in different retinal layers and choriocapillaris after bevacizumab injections using careful segmentation procedures. 5 The authors conducted a case series of consecutive patients who received intravitreal bevacizumab (IVB) for center-involving DME and obtained en face OCTA images at baseline and 1 month after receiving IVB.…”
mentioning
confidence: 99%
“…Similarly, another study by Busch et al which looked at microvascular density post intravitreal aflibercept injections for DME from 3 to 25 months also did not show any differences. 4 Compared with the other two OCTA studies, the present study was conducted on only DME patients with a single anti-VEGF agent and included manual correction of segmentation errors by two graders. Some of the limitations of the present study include a small sample size, short follow up time, and lack of control groups that received other anti-VEGF injections.…”
mentioning
confidence: 99%